The Development of Capital Markets and Economic Growth in Transition Economies: Sabbatical Fall 2009 - Grubacic, Sanja (2009)
This project involved gathering, analyzing, and preparing for publication the new empirical evidence on the working of capital markets in several economies of East and Central Europe, additionally providing material to enrich the curriculum in economics and finance. It also provided material for a conference presentation.
Keywords: dept.eco; faculty_collection

Testing Trade-Off and Pecking Order Models Under Different Institutional Environments - Farhat, Joseph B.; Cotei, Carmen; Abugri, Benjamin A. (SSRN Electronic Journal, 2009)
In this paper, we examine the differences in information asymmetry and financing patterns and a generalized version of the trade-off theory across countries with different institutional environments. We find that firms in Civil law countries have higher information asymmetry, rely more on internally generated funds, and use more short-term debt to finance their financing deficit, relative to those in Common law countries. In both Civil law and Common law countries, factors suggested by the trade-off theory explain the financing deficit coefficient in the generalized version of the trade-off model. Overall, the generalized version of the trade-off theory provides a better explanation for the changes in capital structure relative to the pecking order theory, even in countries with higher information asymmetry.
Keywords: International capital structure; dept.eco; dept.fin; pecking order theory; trade-off theory

The effects of noise and manipulation on the accuracy of collective decision rules - Bodo, Peter (2009)
How do noise and manipulation affect the accuracy of collective decision rules? This paper presents simulation results that measure the accuracy of ten well known collective decision rules under noise and manipulation. When noise is low these rules can be divided into accurate ("good") and inaccurate ("bad") groups. The bad rules' accuracy improves, sometimes significantly, when noise increases while the good rules' performance steadily worsens with noise. Also, when noise increases the accuracy of the good rules deteriorates at different rates. Manipulation delays the effects of noise: Accuracy improvement and deterioration due to noise emerge only at higher noise levels with manipulation than without it. In some cases at high noise levels there is only a negligible difference between the accuracy of good and bad collective decision rules. © 2009 Springer-Verlag Berlin Heidelberg.
Keywords: Accuracy Improvement; Acoustic noise; Collective decision; Collective decision rules; Decision theory; Fluorine containing polymers; Game theory; High noise levels; Higher noise levels; Manipulability; Manipulability of collective decisions; Noise sensitivity; Piezoelectric actuators; Simulation result; dept.eco